2005
DOI: 10.1002/jmri.20462
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying CBF with arterial spin labeling

Abstract: The basic principles of measuring cerebral blood flow (CBF) using arterial spin labeling (ASL) are reviewed. The measurement is modeled by treating the ASL method as a magnetic resonance imaging (MRI) version of a microsphere study, rather than a diffusible tracer study. This approach, particularly when applied to pulsed ASL (PASL) experiments, clarifies that absolute calibration of CBF primarily depends on global properties of blood, rather than local tissue properties such as the water partition coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 12 publications
2
120
0
1
Order By: Relevance
“…Investigators have attempted to validate the blood flow on ASL in the brain (12) and have shown that the blood flow on the ASL is linearly correlated with the blood flow obtained on other confirming methods. Our results showed significant positive correlation between the blood flow on FAIR and various perfusion-related parameters on DCE-MR, including the Kep, percent relative enhancement, and percent enhancement ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have attempted to validate the blood flow on ASL in the brain (12) and have shown that the blood flow on the ASL is linearly correlated with the blood flow obtained on other confirming methods. Our results showed significant positive correlation between the blood flow on FAIR and various perfusion-related parameters on DCE-MR, including the Kep, percent relative enhancement, and percent enhancement ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In ASL, the protons in arterial blood water are electromagnetically labeled proximal to the tissue of interest and the effects of prelabeling are determined by pair-wise comparison with images acquired using control labeling. The rate of decay of the signal from a known band proximal to the tissue of interest can be used qualitatively to compare perfusion of different areas of the brain on the same slice as well as calculate CBF using known parameters of protons in the blood, based on numerical values abstracted from the literature (Buxton, 2005). There are now at least four different variations on ASL including continuous ASL (CASL) (Detre and Alsop, 1999), pulsed ASL (PASL), cPASL (continuous PASL), and velocity selected ASL (VSASL) .…”
Section: Perfusion Imagingmentioning
confidence: 99%
“…Since at TI = 1200 -milliseconds, most of the magnetization remains in the blood (Buxton, 2005), the relaxation time of the arterial blood T 1 = 1930 milliseconds (Stanisz et al, 2005) was uniformly used across all regions. There was no smoothing of ASL images.…”
Section: Calculation Of Blood Flowmentioning
confidence: 99%